Practical Evaluation of a Secure Key-Distribution and Storage Scheme for Wireless Sensor Networks Using TinyOS - Juliano F. Kazienko; Igor G. Ribeiro; Igor M. Moraes; Célio V. N. Albuquerque (CLEI Electronic Journal, 2011)
TinyOS is a major platform broadly used to carry out experiments related to Wireless Sensor Networks (WSNs). A number of researchers claim that cryptographic mechanisms demand plenty of resources from sensors. In this context, an important issue is to develop lightweight encryption mechanisms capable of running in resource-constrained sensors. The main contribution of this work is to carry out an experimental evaluation of a secure key distribution and storage scheme in a WSN using simulation and practical experiments. Through simulation, we verify that this scheme introduces very low processing overhead, in the order of nanoseconds, when compared to existing approaches. Additionally, practical measurements indicate that the scheme can be deployed by off-the-shelf sensor platforms, such as MicaZ and TelosB. The performance metrics considered are the processing time of encryption and decryption functions, the application memory requirements and the power consumption. We have also evaluated several functionalities of the scheme on a real testbed. In summary, this work demonstrates the practical feasibility of implementing such scheme in real sensor networks.